1996
DOI: 10.1111/j.1749-6632.1996.tb44778.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial Characterization of the Feline Sodium‐Calcium Exchanger Genea

Abstract: The sodium-calcium exchanger plays a key role in calcium efflux and, therefore, in the control and regulation of intracellular calcium in the cardiocyte. We have previously shown the exchanger to be acutely sensitive to changes in pressureinduced load; one hour of pressure overload produces a two-to-fourfold increase in the level of exchanger mRNA. Maintenance of this load for forty-eight hours results in increased exchanger pr0tein.l Message half-life analysis implicates a translational start, respectively, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…As a result of alternative promoter usage and the resulting alternative splicing, there are multiple tissue-specific variants of NCX1 (Barnes et al 1997; Lee et al 1994; Kofuji et al 1993; Quednau et al 1997). In our initial characterization of the NCX1 cardiac promoter (Barnes et al 1996, 1997), we demonstrated that a construct containing the first 250 bp of the 5′-flanking region, H1 exon, and 67 bp of the first intron is sufficient for cardiac-directed expression and α-adrenergic stimulation of the luciferase reporter gene. We have since shown that a construct containing only 184 bases of the 5′- flanking region, H1 exon, and 67 bp of the first intron is not only sufficient for cardiac-directed expression but also for α-adrenergic stimulation of the luciferase reporter gene (Xu et al 2006).…”
Section: 2 α-Adrenergic Receptor-stimulated Ncx1 Upregulationmentioning
confidence: 99%
“…As a result of alternative promoter usage and the resulting alternative splicing, there are multiple tissue-specific variants of NCX1 (Barnes et al 1997; Lee et al 1994; Kofuji et al 1993; Quednau et al 1997). In our initial characterization of the NCX1 cardiac promoter (Barnes et al 1996, 1997), we demonstrated that a construct containing the first 250 bp of the 5′-flanking region, H1 exon, and 67 bp of the first intron is sufficient for cardiac-directed expression and α-adrenergic stimulation of the luciferase reporter gene. We have since shown that a construct containing only 184 bases of the 5′- flanking region, H1 exon, and 67 bp of the first intron is not only sufficient for cardiac-directed expression but also for α-adrenergic stimulation of the luciferase reporter gene (Xu et al 2006).…”
Section: 2 α-Adrenergic Receptor-stimulated Ncx1 Upregulationmentioning
confidence: 99%